Talpapellis solorinae sp. nov. and an updated key to the species of Talpapellis and Verrucocladosporium - Zhurbenko, Mikhail P.; Heuchert, Bettina; Braun, Uwe (Phytotaxa, 2015)
The genus Talpapellis Alstrup & M.S.Cole (1998: 227) was introduced for a lichenicolous hyphomycete on Peltigera venosa collected in British Columbia, Canada (Alstrup & Cole 1998). Details of the conidiogenesis, the generic affinity and application of this genus name have previously been unclear and largely confused. Based on a revision and reassessment of type material and examination of additional collections from North America and Asia, Heuchert et al. (2014) published an amended circumscription of Talpapellis, discussed the conidiogenesis of this genus, described a new variety of T. peltigerae Alstrup & M.S.Cole (1998: 227) and provided a key to the recognised taxa of Talpapellis and confusable species of Verrucocladosporium K.Schub. et al. (Crous et al. 2007, Braun et al. 2009).